Prevalence of IgG antibodies against Malawi polyomavirus in patients with autoimmune diseases and lymphoproliferative disorders subjected to bone marrow transplantation - Nicol, Jérôme T. J.; Mazzoni, Elisa; Iaquinta, Maria Rosa; De Pace, Raffaella; Gaboriaud, Pauline; Maximova, Natalia; Cason, Carolina; De Martino, Eleonora; Mazziotta, Chiara; Coursaget, Pierre; Touzé, Antoine; Boz, Valentina; et al. (Frontiers in Immunology, 2024)
Introduction Human polyomaviruses (HPyVs) cause persistent/latent infections in a large fraction of the population. HPyV infections may cause severe diseases in immunocompromised patients. Malawi polyomavirus (MWPyV) is the 10th discovered human polyomavirus (HPyV 10). MWPyV was found in stool samples of healthy children. So far, the few investigations carried out on HPyV 10 did not find an association with human disease. Methods In this study, to verify the putative association between MWPyV and human diseases, MWPyV seroprevalence was investigated in patients affected by i) lymphoproliferative disorders (LPDs) and ii) immune system disorders, i.e., autoimmune diseases (ADs), and in iii) healthy subjects. An indirect ELISA, employing virus-like particles (VLPs) to detect serum IgG antibodies against MWPyV/HPyV 10, was carried out. The study also revealed the prevalence of another polyomavirus, Merkel cell polyomavirus (MCPyV). Results Sera from patients with distinct autoimmune diseases (n = 44; mean age 20 years) had a prevalence of MWPyV antibodies of 68%, while in patients with lymphoproliferative disorders (n = 15; mean age 14 years), subjected to bone marrow transplantation, the prevalence was 47%. In healthy subjects (n = 66; mean age 13 years), the prevalence of MWPyV antibodies was 67%. Our immunological investigation indicates that MWPyV/HPyV 10 seroconversion occurs early in life and MWPyV/HPyV 10 appears to be another polyomavirus ubiquitous in the human population. A significantly lower MWPyV antibody reactivity together with a lower immunological profile was detected in the sera of LPD patients compared with HS2 (*p < 0.05) (Fisher’s exact test). LPD and AD patients have a similar MCPyV seroprevalence compared with healthy subjects. Discussion MWPyV seroprevalence indicates that this HPyV is not associated with lymphoproliferative and autoimmune diseases. However, the ability to produce high levels of antibodies against MWPyV appears to be impaired in patients with lymphoproliferative disorders. Immunological investigations indicate that MWPyV seroconversion occurs early in life. MCPyV appears to be a ubiquitous polyomavirus, like other HPyVs, in the human population.